A facile method to prepare a wearable pressure sensor based on fabric electrodes for human motion monitoring. Issue 23 (December 2019) - Wu, Ronghui; Ma, Liyun; Balkrishna Patil, Aniruddha; Hou, Chen; Meng, Zhaohui; Zhang, Yifan; Liu, Xiangyang; Yu, Weidong
Intelligent textile that endow traditional fabric with functionalities have attracted increasing attention. In this research work, we fabricated a flexible and wearable pressure sensor with conductive nylon fabric as the electrodes and elastomer Ecoflex as the dielectric layer. The conductive nylon fabric in the twill structure, which showed a high conductivity of 0.268 Ω·cm (specific resistance), was prepared by magnetron sputtering with silver films. The flexible pressure sensor shows a high sensitivity of 0.035 kPa −1, a good linear response under pressure from 0 to 16 kPa, and a quick response time of 0.801 s. The fabricated pressure sensor was found to be highly reproducible and repeatable against repeated mechanical loads for 9500 times, with a small capacitance loss rate of 0.0534. The fabric-based flexible and wearable sensor with good properties can be incorporated into a fabric garment by the hot-pressing method without sacrificing comfort, which can then be used for human motion detecting or touch sensing. The smart glove with finger touch function was proved to be efficient in Morse code editing, which has potential for information transfer in the military field.